Analisis Strategi Membanteras Rasuah Menurut Islam - Sanusi, Afriadi; Syed Ismail, Sharifah Hayaati (Online Journal of Research in Islamic Studies, 2016)
Many people believe about what and how corruption in the view of Islam in guidance by al-Quran and Sunnah. Al-Quran and Sunnah also explains how to eradicate corruption by Islamic approach. Because almost all Muslim countries currently hit by the disease of corruption, then it would be nice if every country to emulate the approach taken by the Prophet, Sahabat and the tabi’in in fighting corruption in their days. This is a qualitative study that collects data through a variety of methods of literature review, historical method and content analysis of primary sources including tafsir, hadith, turath, books and articles in journals.